BIRT 2.6 data analysis and reporting : create, design, format, and deploy reports with the world's most popular Eclipse-based business intelligence and reporting tool /: create, design, format, and deploy reports with the world's most popular Eclipse-based business intelligence and reporting tool. (2010) - Unknown
No abstract available